Vessel-Length distribution in stems of rattan (Calamus SPP.) - Ashaari, Zaidon; Sahri, Mohd Hamami (Universiti Putra Malaysia Press, 1999)
Vessel-length distributions in the stems of rotan manau (Calamus manan Miq.), rotan dok (c. omatus Blume) and rotan jelayang (c. peregrinus Furtado) have been calculated from measurements ofparticle penetration. Due to the limitation of the length of the samples, the longest class of vessel determined was below 40 cm. Approximately, 71-80% of the vessels that were counted for the rattan stems were more than 36 cm long. The largest percentage of vessel in this class was Calamus manan followed by C. peregrinus and C. omatus. The shortest vessel-length distributed was in the class of 6-9 cm long which constituted 27% of the vessels counted in the stem of C. peregrinus. The shortest vessel-length distributed respectively in C. manan and C. omatus were in the class of 9-12 cm long (6%) and 12-15 cm long (8%). The shorter vessels found distributed in the rattan stems could either be the vessels that end orform bridges at the leaf trace complex near the leaf base (nodal section) or could be the smaller metaxylem vessels that are distributed near the periphery of the rattan stem. The appropriate way of estimating the distribution of vessel-length of any stem is to use sample in the experiment longer than the longest available vessel.